Analytical Study on the Efficacy of Neoadjuvant Chemotherapy Using a Combination of Methotrexate, Bleomycin, and Cisplatin in the Management of Advanced Squamous Cell Carcinoma of the Buccal Mucosa - Kumar, Santosh Manohar; Biswas, Srabani; Sarkar, Shreya; Mandal, Syam Sundar; Biswas, Jaydip (Indian Journal of Medical and Paediatric Oncology, 2017)
Context: Cancers of the buccal mucosa (CaBM) predominate in India with late- stage diagnosis and poor survival, necessitating optimal management. Aim: Our study aimed at testing the efficacy of combination neoadjuvant chemotherapy (NACT) using cisplatin (CIS), bleomycin (BL) and methotrexate (MTX) for reducing tumour volume prior to surgery. Methodology: Patients with advanced CaBM (stage III, IV, n = 100) were administered 6 rounds of NACT with CIS, BL and MTX. Responses, toxicity and 6-month follow-up was monitored statistically to determine persistence of response. Results: A significant number of patients showed objective response as either complete or partial tumour regression with subjective response as reduced trismus, pain, salivation and foul odour. Moreover, there was mild associated toxicity and tumour regression continued in most patients even after 6-month follow-up. Conclusion: Our study indicates that NACT with CIS, BL and MTX offers a good therapeutic alternative in terms of significant objective and subjective responses, low toxicity, affordable costs and persistent responses.
Keywords: Bleomycin; cisplatin; methotrexate; neoadjuvant chemotherapy; objective response